2016
DOI: 10.1017/s1041610216002179
|View full text |Cite
|
Sign up to set email alerts
|

Memory for emotional images differs according to the presence of depressive symptoms in individuals at risk for dementia

Abstract: Results support previous research suggesting that the neuropsychological profile of aMCI/D+ is different from that of aMCI and LLD. Although depressed and non-depressed individuals with aMCI recall comparable quantities of information, the quality of the recalled information differs significantly. On theoretical grounds, this suggests the existence of distinct neurobiological or neurofunctional manifestations in both groups. Practically, these differences may guide the development of personalized emotion-focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The only study of the SRE in aMCI to investigate valence (Leblond et al, 2016) indicated that while healthy controls showed no valence preferences, individuals with aMCI exhibited the SRE specifically for positive trait adjectives. This finding is consistent with other research that has shown a positivity bias in aMCI (Brueckner & Moritz, 2009;Callahan et al, 2016 [immediate recall]; Werheid et al, 2010) but inconsistent with other studies indicating a negativity bias (Mah, Anderson, Verhoeff, & Pollack, 2017) or no difference for positive and negative material over neutral stimuli in aMCI (Callahan, Laforce, Dugas, & Hudon, 2017).…”
supporting
confidence: 77%
“…The only study of the SRE in aMCI to investigate valence (Leblond et al, 2016) indicated that while healthy controls showed no valence preferences, individuals with aMCI exhibited the SRE specifically for positive trait adjectives. This finding is consistent with other research that has shown a positivity bias in aMCI (Brueckner & Moritz, 2009;Callahan et al, 2016 [immediate recall]; Werheid et al, 2010) but inconsistent with other studies indicating a negativity bias (Mah, Anderson, Verhoeff, & Pollack, 2017) or no difference for positive and negative material over neutral stimuli in aMCI (Callahan, Laforce, Dugas, & Hudon, 2017).…”
supporting
confidence: 77%
“…Results showed a pooled effect size estimate of g = 0.28, 95% CI [0.20, 0.37], 95% PI [−1.21, 1.78], p < .001. Statistical outlier analysis identified nine contrasts from four independent samples (Callahan et al, 2017; Dozois & Dobson, 2001b; Moulds et al, 2007; Sloan et al, 2001) with standardized residual values exceeding 3 (Aguinis et al, 2013; Viechtbauer & Cheung, 2010). These outlying effect size estimates may impact the precision and interpretation of the overall effect size and were excluded from subsequent analyses.…”
Section: Resultsmentioning
confidence: 99%
“… No mention of exclusion criteria Vallet et al ( 207 ) Québec 16 M = 78.19, SD = 6.1 F: 11 (68.75%) M: 5 (31.25%) M = 14.94, SD = 4.10 Petersen ( 18 , 23 ) M =28.31, SD = 1.5 M =25.62, SD = 2.1 Observ. Exclusion: Medical history of or currently taking medications for conditions with known sensory or neurological effects; participants with diagnoses of depression and/or anxiety were included if they were stable on medication or non-symptomatic at the time of study Bocti et al ( 208 ) Québec 42 M = 69.62, SD = 9.31 F: 20 (47.62%) M: 22 (52.38%) M = 12.27, SD = 5.07 Chertkow et al ( 130 ) M =27.93, SD = 1.83 M =23.22, SD =3.86 Cross-sect Exclusion: severe psychiatric or systemic disorder, cognitive impairment attributed to large vessel stroke, TBI, alcohol abuse, sleep apnea, or cancer and related treatment Callahan et al ( 209 ) Québec …”
Section: Appendicesmentioning
confidence: 99%